Natural human infections with plasmodium cynomolgi and other malaria species in an elimination setting in Sabah, Malaysia - Lynn Grignard; Sonal Shah; Chua, Tock Hing; Timothy William; Chris J. Drakeley; Kimberly M. Fornace (Oxford University Press, 2019)
To determine the presence and species composition of malaria infections, we screened a subset of samples collected during a cross-sectional survey in Northern Sabah, Malaysia using highly sensitive molecular techniques. Results identified 54 asymptomatic submicroscopic malaria infections, including a large cluster of Plasmodium falciparum and 3 P. knowlesi infections. We additionally identified 2 monoinfections with the zoonotic malaria Plasmodium cynomolgi, both in individuals reporting no history of forest activities or contact with macaques. Results highlight the need for improved surveillance strategies to detect these infections and determine public health impacts.